2020
DOI: 10.7717/peerj.9062
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate solubilizing bacteria stimulate wheat rhizosphere and endosphere biological nitrogen fixation by improving phosphorus content

Abstract: Phosphate (P) availability often limits biological nitrogen fixation (BNF) by diazotrophic bacteria. In soil, only 0.1% of the total P is available for plant uptake. P solubilizing bacteria can convert insoluble P to plant-available soluble P (ionic P and low molecular-weight organic P). However, limited information is available about the effects of synergistic application of diazotrophic bacteria and P solubilizing bacteria on the nitrogenase activity of rhizosphere and nifH expression of endosphere. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 46 publications
1
18
1
1
Order By: Relevance
“…This is because several metabolic processes that occur in plant cells notably, ammonium assimilation into amino acids and ureides were also found to be critically affected by P concentration (Batterman et al, 2013;Singh et al, 2013;Mitran et al, 2018). Li et al (2020) found that increasing P content in soil and wheat (Triticum aestivum) plant tissues also enhanced total N and nitrogenase activity in plant shoots and roots along with nifH gene expression, supporting our understanding of the role of P in the enhancement of BNF (Wani et al, 2007).…”
Section: Importance Of P In Legume Bnfmentioning
confidence: 61%
See 3 more Smart Citations
“…This is because several metabolic processes that occur in plant cells notably, ammonium assimilation into amino acids and ureides were also found to be critically affected by P concentration (Batterman et al, 2013;Singh et al, 2013;Mitran et al, 2018). Li et al (2020) found that increasing P content in soil and wheat (Triticum aestivum) plant tissues also enhanced total N and nitrogenase activity in plant shoots and roots along with nifH gene expression, supporting our understanding of the role of P in the enhancement of BNF (Wani et al, 2007).…”
Section: Importance Of P In Legume Bnfmentioning
confidence: 61%
“…In fact, BNF as one of the main rhizosphere biological processes, is correlated with P availability wherein P deficiency strongly limits the activity of diazotrophic (i.e., N 2 -fixing bacteria), reduces the symbiotic partnership between plant host and rhizobia, as well as the N 2 -fixation process itself (Aziz et al, 2016;Martins et al, 2017;Sanz-Saez et al, 2017;Li et al, 2020;Tewari et al, 2020). Tewari et al (2020) further highlighted the role of P as a structural element in controlling the BNF process.…”
Section: Importance Of P In Legume Bnfmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the well-documented action of phosphate-solubilizing and nitrogen-fixing microorganisms in plant P and N nutrition [ 13 , 14 ], the importance of microbial activity on plant K nutrition is less well understood. It has been shown that bacteria and mycorrhizal fungi do solubilize mineral K by various mechanisms such as production of alkaline substances including ammonia and other metabolites upon death of microbial cells and subsequent proteolysis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%